Electrolyte Engineering Stabilizes Photoanodes Decorated with Molecular Catalysts - Jenewein, Ken (2023)
Molecular catalysts are promising oxygen evolution promoters in conjunction with photoanodes for solar water splitting. Maintaining the stability of both photoabsorber and cocatalyst is still a prime challenge, with many efforts tackling this issue through sophisticated material designs. Such approaches often mask the importance of the electrode-electrolyte interface and overlook easily tunable system parameters, such as the electrolyte environment, to improve efficiency. We provide a systematic study on the activity-stability relationship of a prominent Fe2O3 photoanode modified with Ir molecular catalysts using in situ mass spectroscopy. After gaining detailed insights into the dissolution behavior of the Ir cocatalyst, a comprehensive pH study is conducted to probe the impact of the electrolyte on the performance. An inverse trend in Fe and Ir stability is found, with the best activity-stability synergy obtained at pH 9.7. The results bring awareness to the overall photostability and electrolyte engineering when advancing catalysts for solar water splitting.